A STUDY ON THE INHIBITORY EFFECT OF SOLANUM LYRATUM THUNB EXTRACT ON LEWIS LUNG CARCINOMA LINES - Xiao, Zhi-Ming; Wang, Ai-Min; Wang, Xiao-Yan; Shen, Shou-Rong (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to observe the effects of Solanum lyratum Thunb extract on tumour inhibition, immune function and survival time of tumour-bearing mice. Lung carcinoma-bearing mouse model was established, the tumour-bearing mice were divided into model group, CTX group, Solanum lyratum Thunb extract high-dose group and low-dose group. By the examination of tumour inhibition rate of Solanum lyratum Thunb extract in Lewis lung carcinoma-bearing mice and determination of the number of NK cells and T cell subsets, the survival rate of tumour-bearing mice was observed. Solanum lyratum Thunb extract had some anti-tumour effect in Lewis tumour-bearing mice. The tumour inhibition rate of high-dose group reached 46.28%, and the tumour inhibition rate of low-dose group was 31.42%. Solanum lyratum Thunb extract can improve the NK cell activity of Lewis tumour-bearing mice, increase the number of CD4 cells in the tumour-bearing mice, and significantly increase the survival rate of tumour-bearing mice. The study concluded that Solanum lyratum Thunb extract has some anti-tumour effect and can improve immune function and survival rate of tumour-bearing mice.